Safe Investment Opportunities during COVID-19 - Raj, Manas; Singh, Kushagra Pratap; Chandra, Manjeet; Kumar, Ramarcha (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The global financial and economic crises continue to be a contentious topic among investors. There are those who can spot and seize investment opportunities, and there are those who are skilled at investing in difficult economic conditions and can create opportunities even in the most difficult crises. When the coronavirus first appeared in China, it quickly spread over the world, wreaking havoc on numerous global financial and economic markets. By researching the effect of the coronavirus on the returns of the cryptocurrency currency and global metals markets traded in the US dollar, this article intends to shed light on investment opportunities in global markets in light of the spread of the coronavirus around the world. , by looking at the impact of the coronavirus on the returns of cryptocurrency and global commodities markets traded in US dollars, where the research period was set depending on the virus’s propagation at a certain level. The world, from March 25, 2020 to June 25, 2020, with Bitcoin, Ethereum, and Tether as the top digital currencies in terms of market value and trading during the research period, and gold, silver, and copper as the best metals in terms of popularity and trading. The number of daily cases, cumulative cases, and daily and cumulative deaths, as well as the number of daily and cumulative deaths, were used to assess the spread of Coronavirus in 213 countries throughout the world. The daily returns of the investment opportunities chosen in each market served as the dependent variable, and the dependent variable in the cryptocurrency and metal markets was assessed by the daily returns of the investment possibilities picked in each market. The findings of the study revealed that the spread of the coronavirus has an impact on cryptocurrency currency markets, with the independent variable (Total Deaths) having the greatest influence on all investment opportunities in the cryptocurrency market. In the metals market, the Total Deaths variable had higher influence on Gold, whereas the Total Cases variable had more influence on Silver and Copper. The findings also revealed that the average return on investment for bitcoin currency markets and metal markets did not differ statistically significantly. The results also revealed that there were no statistically significant differences between the average return on investment for cryptocurrency currency markets and metal markets, with the significance of the test reaching (0.889), which is greater than the level of significance of 5%, due to the convergence of market average levels during the period of global coronary virus spread. The best investment opportunities during the research period, according to the return-on-investment index, were Ethereum (72.02 percent), Bitcoin (38.98 percent), and Tether (0.23 percent) in the cryptocurrency currency markets, and Silver (42.16 percent), Copper (20.75 percent), and Gold (0.23 percent) in the metal markets (8.54 percent).